Doing Sociology With People: Disability, Coloniality and Reflexivity in Institutional Ethnography - Abass Isiaka (Forum: Qualitative Social Research)
In this paper, I offer an embedded approach to reflexivity in institutional ethnography (IE). I draw on a study conducted with disabled students in a post-colonial higher education context to show why and how existing approaches to reflexivity in IE have been inadequate in preserving the voice of subaltern subjects. I engage with the question of what reflexivity means for "academic homecomer[s]" (ORIOLA & HAGGERTY, 2012) who have been educated in the global North, going to research in the South. By proposing a decolonial IE that demands biographical, epistemic, analytical and transformational reflexivity, I advance the arguments for IE to move from a "sociology for people" (SMITH, 2005) to a sociology with people who are being ruled by the "colonial matrix of power" relations (MIGNOLO & WALSH, 2018, p.4). With a decolonial IE, I take a reflexive approach to understanding how the trans-local conditions of coloniality coordinate the social relations of inclusion and participation for disabled students. I conclude that while IE allows the opportunity to empower those being ruled by a matrix of domination with the knowledge of how things are organised, like some other participatory research, it does not offer researchers a way to work with the people on how to transform their everyday actualities.